Women priesthood in the Philippine Independent Church : a faith-seeking justice - Maga, Erahvilla M. (Quezon City : St. Andrew's Theological Seminary, 1989)
This paper is an effort to look into the roots of the invisibility, subordination or subjugation of women in the church: myth, tradition, concept, and some biblical verses that are used to justify such status of women. On the other hand, it also looks into "the how" women are being liberated from such status: its biblical and theological foundations and re-reading the scriptures from the women's point of view. Here, the church is asked regarding its mission in the world being the body of Christ (Eph. 5:23b).
Submitted to the faculty as partial fulfillment for the degree of Bachelor in Theology
Thesis (B.Th.)-- St. Andrew's Theological Seminary